2007
DOI: 10.1111/j.1750-3841.2007.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity of Proteolytic Hydrolysates of the Soybean 11S Globulin

Abstract: A substantial portion of the human population has immune hypersensitivities to various food materials. Soybean is one of the most common foods involved in such hypersensitivity reactions, especially in younger children. In this study, we investigated the effect of peptic and chymotryptic hydrolysis on the allergenicity of the 11S soybean globulin, which is the primary soybean allergen. The 11S globulin is composed of both acidic and basic polypeptides, and we found that the acidic polypeptide was effectively h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…However, other studies [25,26,27] have shown that Ara h 3 basic subunits may be important allergenic peptides. The resistance of the 11S globulin basic subunit to enzymatic hydrolysis has been reported previously in soybeans [28]. …”
Section: Discussionmentioning
confidence: 97%
“…However, other studies [25,26,27] have shown that Ara h 3 basic subunits may be important allergenic peptides. The resistance of the 11S globulin basic subunit to enzymatic hydrolysis has been reported previously in soybeans [28]. …”
Section: Discussionmentioning
confidence: 97%
“…The IgE binding capacity of soy glycinin is reported not to be affected by heating [17], while sequential hydrolysis by pepsin and chymotrypsin is reported to result in peptides of 20 kDa and smaller, with a 20 kDa peptide still being able to bind IgE [18]. The effects of heating and digestion on the IgE binding capacity of Ara h 3 have not been investigated yet.…”
Section: Introductionmentioning
confidence: 96%
“…Although most food allergens maintain their activity after passing through the digestive tract, the relationship between food allergenicity and digestibility is still unclear. Stability to denaturation and proteolysis, and potential for aggregation seem to be important factors, as well as allergen concentration (Lee et al, 2007;Van Boxtel et al, 2008).…”
Section: Allergenicity Of Pulse Proteinsmentioning
confidence: 99%